2016
DOI: 10.3390/su8040377
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Location-Based Priority of Soil and Groundwater Pollution Remediation

Abstract: Abstract:Under the circumstances of limited government funds, the future pollution remediation policies and practical implementation may need contemplation from the perspective of maximized efficacy, in order to pursue the most effective resource allocation. In fact, different pollution sources and types affect the value of surrounding properties differently in significance and scope. Therefore, benefits from the remediation may vary depending on the polluted locations. Currently, however, decision-making on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Thus, the goal constituted one cluster with node G while the remediation alternatives (RA) (that is, the chosen remediation methods) made up another cluster with four nodes, namely; landfarming (LDF), field biopiles (FBS), thermal desorption (TDU), and phytoremediation (PHY) as shown in Figure 2. From a number of open access literatures on bioremediation we were able to access (e.g., Linkov et al, 2005;Oduolisaeme, 2012;Frutos et al, 2012;Smith et al, 2015;Li et al, 2016;Azubuike et al, 2016), the remaining four clusters (selection criteria)health and safety (HS), site-specific characteristics (SC), regulatory requirements (RR), and technical feasibility (TF)and their sub-criteria (or elements) shown in Figure 2 were considered. As can be seen in Figure 2, RA was taken as the dependent variable while the independent variables were HS, SC, RR, and TF as well as their sub-criteria.…”
Section: Problem Structuringmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the goal constituted one cluster with node G while the remediation alternatives (RA) (that is, the chosen remediation methods) made up another cluster with four nodes, namely; landfarming (LDF), field biopiles (FBS), thermal desorption (TDU), and phytoremediation (PHY) as shown in Figure 2. From a number of open access literatures on bioremediation we were able to access (e.g., Linkov et al, 2005;Oduolisaeme, 2012;Frutos et al, 2012;Smith et al, 2015;Li et al, 2016;Azubuike et al, 2016), the remaining four clusters (selection criteria)health and safety (HS), site-specific characteristics (SC), regulatory requirements (RR), and technical feasibility (TF)and their sub-criteria (or elements) shown in Figure 2 were considered. As can be seen in Figure 2, RA was taken as the dependent variable while the independent variables were HS, SC, RR, and TF as well as their sub-criteria.…”
Section: Problem Structuringmentioning
confidence: 99%
“…Despite the widespread application of ANP in other fields, only a limited number of studies can be found in the open access literature on the application of ANP in the evaluation of petroleum contaminated site remedial countermeasures (Promentilla et al, 2006;Yang et al, 2010;Banar et al, 2015;Li et al, 2016). In Nigeria, there is no method currently adopted to tackle the challenge of petroleum contaminated site management.…”
Section: Introductionmentioning
confidence: 99%